Comparative Analyses of Turkish Variome and Widely Used Genomic Variation Databases for the Evaluation of Rare Sequence Variants in Turkish Individuals: Idiopathic Hypogonadotropic Hypogonadism as a Disease Model - Leman Damla Kotan (Galenos Yayincilik, 2022)
INTRODUCTION: With the increasing use of whole-exome sequencing, one of the challenges in identifying the causal allele for a Mendelian disease is the lack of availability of population-specific human genetic variation reference databases. The people of Turkey were not represented in GnomAD or other publicly available large databases until recently, when the first comprehensive genomic variation database, Turkish Variome (TRV), was published. The aim of this study was to evaluate whether TRV or other publicly available large genomic variation databases can reliably be used for rare disease variant evaluation in Turkish individuals. METHODS: Sixty non-disease-causing, non-synonymous variants (minor allele frequencies >1%) were identified in 58 genes that are known to be associated with idiopathic hypogonadotropic hypogonadism from a large Turkish patient cohort. The allelic frequencies of these variants were then compared with those in various public genomic variation databases, including TRV. RESULTS: Our cohort variants showed the highest correlations with those in the TRV, Iranome, and The Greater Middle East Variome, in decreasing order. DISCUSSION AND CONCLUSION: These results suggest that the TRV is the appropriate database to use for rare genomic variant evaluations in the Turkish population. Our data also suggest that variomes from geographic neighborhoods may serve as substitute references for populations devoid of their own genomic variation databases.